Pengembangan Media Pembelajaran Bahasa Arab Berbasis Kartu UNO Siswa Madrasah Tsanawiyah Opu Daeng Risaju Palopo - Hardyanti Safirah Amran; M. Zuhri Abu Nawas; Mubassyirah Bakri (STIKes Ibnu Sina Ajibarang, 2025)
This study addresses the development of Uno card-based learning media to support vocabulary acquisition among eighth-grade students. It focuses on two main issues: the effectiveness of the media in enhancing vocabulary comprehension and the challenges encountered during its development, particularly in relation to learning motivation. The primary goal is to evaluate the extent to which this media aids vocabulary learning and to identify any obstacles in the development process. The research follows the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. To ensure the validity of the learning media, expert validation was conducted by media, content, and educational professionals. Additionally, student questionnaires were distributed to assess the media’s effectiveness. The validation results showed that the content expert gave a score of 83%, the media expert 81%, and student responses reached 88%, indicating strong acceptance and usability. The effectiveness of the media was further supported by the pre-test and post-test results, with a Normalized Gain score of 61.01%, categorized as